Electron Microscopy Findings in N-Methyl-N-Nitrosourea-Induced Mammary Tumors. (22nd September 2016) - Faustino-Rocha, Ana I.; Calado, Ana M.; Gama, Adelina; Ferreira, Rita; Ginja, Mário; Oliveira, Paula A.
Abstract: Although the rat model of mammary tumors chemically induced by N -methyl- N -nitrosourea (MNU) has been frequently used by several research teams, there is a lack of ultrastructural studies in this field. The main aim of this work was to perform an ultrastructural characterization of MNU-induced mammary tumors in female rats. Some alterations previously reported in human mammary tumors, such as nucleus size and shape, accumulation of heterochromatin in the perinuclear region, and interdigitating cytoplasmic processes between cancer cells were also observed in MNU-induced mammary tumors. Although a low number of samples were analyzed by transmission electron microscopy in the present study, we consider that it may contribute to a better understanding of MNU-induced mammary carcinogenesis in a rat model. The ultrastructural characteristics of the two most frequently diagnosed mammary carcinomas described in the present work can be useful to differentiate them from other histological patterns. In addition, the loss of cytoplasm in neoplastic cells and formation of vacuoles were described.